2010
DOI: 10.1021/jp109260g
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Hydrogen Storage Properties of Dual-Cation (Li, Ca) Borohydride

Abstract: Lithium borohydride, LiBH 4 , possesses high hydrogen capacity, but cannot be used for hydrogen storage owing to the problematic H-exchange kinetics and thermodynamics. In the present study, we employed the Li + -Ca 2+ combination strategy to improve the de/rehydrogenation properties of LiBH 4 . Our study found that mechanically milling 1:1 LiBH 4 /Ca(BH 4 ) 2 mixture formed a dual-cation borohydride, Li 0.9 Ca(BH 4 ) 2.9 , which then transformed to stoichiometric LiCa(BH 4 ) 3 in the heating process. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
(103 reference statements)
1
27
0
Order By: Relevance
“…At the room temperature T = 298 K, the reaction (2) was predicted 14,15 to occurs at the hydrogen pressure P H 2 from 10 3 to 10 7 bar. As the minimum hydrogen pressure P min H 2 = 10 3 bar was predicted for the Cmcm phase, this parameter can be estimated for other low-energy structures of NaSc(BH 4 ) 4 assuming that there is no change in the products of the reaction (2). Hence, the change of the Gibbs energy ∆G(T ) is given by the change in the Helmholtz free energies, calculated at the PBE level and shown in Table II.…”
Section: B Minima-hopping Predicted Low-energy Structuresmentioning
confidence: 99%
“…At the room temperature T = 298 K, the reaction (2) was predicted 14,15 to occurs at the hydrogen pressure P H 2 from 10 3 to 10 7 bar. As the minimum hydrogen pressure P min H 2 = 10 3 bar was predicted for the Cmcm phase, this parameter can be estimated for other low-energy structures of NaSc(BH 4 ) 4 assuming that there is no change in the products of the reaction (2). Hence, the change of the Gibbs energy ∆G(T ) is given by the change in the Helmholtz free energies, calculated at the PBE level and shown in Table II.…”
Section: B Minima-hopping Predicted Low-energy Structuresmentioning
confidence: 99%
“…Reports on the structure and hydrogen storage properties of the LiBH 4 -Ca(BH 4 ) 2 composite have been published [48,49]. Accounts of the nature of the LiBH 4 -Ca(BH 4 ) 2 mixtures differ, however, as Z. Fang et al reported on the formation of a dual-cation borohydride LiCa(BH 4 ) 3 , while J. Y. Lee et al concluded that LiBH 4 and Ca(BH 4 ) 2 coexist as a physical mixture but not as a compound or a solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting suitable geometries that do not rely on dispersion interactions and making trend statements can be achieved at lower costs. [34][35][36][37] Therefore, as long as one stays away from calculating exact energies with a claim of chemical accuracy, one can reliably apply mainstream quantum chemical calculations to zeolite models to evaluate trends.…”
Section: Modeling Of Hydrocarbon Interactionsmentioning
confidence: 99%